Label-free Electrochemical Nanobiosensors Using Au-SPE for COVID-19 Detection: A Comparative Review of Different Biomarkers and Recognition Elements - Kangarshahi, Babak M.; Naghib, Seyed Morteza (Current Analytical Chemistry, 2024)
An immediate and precise diagnosis is required due to the COVID-19 outbreak. Labelfree electrochemical biosensors show promise as potentially valuable instruments for detecting COVID-19. These biosensors are distinguished by their lack of complexity, high speed, sensitivity, and relatively low cost. The precise COVID-19 biomarkers may be recognized without labeling or amplification by detecting the electrical signal created by direct contact between the target analyte and the identification element positioned on the electrode surface. This can be done by placing the electrode in contact with the target analyte, which will amplify the signal. It has been shown that using gold screen printed electrodes, also known as Au SPE, is beneficial when used as an electrode material in label-free electrochemical biosensors. This review study examines and contrasts the performance of several label-free electrochemical biosensors that use Au SPE to detect COVID-19. The merits and limitations of each biosensor will also be discussed. These biosensors use recognition components like DNA, RNA, antibody, aptamer, and MIP and depend on various indicators, such as viral RNA, viral protein, and host antibody. In addition, an analysis of the difficulties and possibilities that may present within this burgeoning subject is carried out. This includes the enhancement of sensor selectivity and stability, optimizing sensor manufacture and design, integrating the sensor with portable readout equipment, and validating the sensor's effectiveness via the use of genuine clinical samples. It can be reasoned out that label-free electrochemical biosensors that make use of gold screen-printed electrodes (Au SPE) have a significant amount of potential for the detection of COVID-19. However, further study is required to address various difficulties, improve their dependability, and broaden the range of applications for these technologies.
Keywords: COVID-19 detection